Seasonal hypoxia and temperature inversions in a tropical bay. Issue 10 (3rd August 2022) - Adelson, Anne E.; Altieri, Andrew H.; Boza, Ximena; Collin, Rachel; Davis, Kristen A.; Gaul, Alan; Giddings, Sarah N.; Reed, Victoria; Pawlak, Geno
Abstract: Dissolved oxygen (DO) is a critically important ecological variable, and the prevalence of marine hypoxia is expected to increase due to the combined effects of ocean warming and eutrophication. Thermal stress can co‐occur with hypoxia, especially in tropical systems, and can exacerbate its effects. We examine the physical processes that are important in regulating hypoxia and temperature inversions in Bahía Almirante, a semi‐enclosed tropical embayment on the Caribbean coast of Panama. A 10‐yr record of observations at 7 locations within Bahía Almirante reveals seasonal temperature inversions and hypoxia at depth that often co‐occur. These features are more severe and persistent in the back bay, though they occur throughout Bahía Almirante. DO reductions correspond to periods with high freshwater input, including direct precipitation, resulting in strong salinity stratification that isolates bottom waters, allowing biological oxygen demand to draw down DO. Evidence indicates that lateral advection can contribute to reoxygenation events, and the relationship between near bottom DO and bottom salinities in the mid bay and back bay is consistent with deep‐water renewal as the mechanism for bottom water ventilation. These hypoxia and temperature inversion events impact the biological communities of Bahía Almirante, and the physical dynamics that regulate these coincident and persistent stressors for marine organisms are likely present in other shallow, tropical estuaries.